2017
DOI: 10.1039/c7ob01959a
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive circularly polarized luminescence from an achiral perylenyl dyad

Abstract: Stimuli-responsive circularly polarized luminescence (CPL) was successfully achieved through fine-tuning the conformation of a perylenyl dyad by using external stimuli. Monomer CPL was clearly detected from an inherent achiral monochromophore system in a simple perylene-carbazole dyad, and concentration-dependent CPL was observed from 'good solvent', giving an excimer-like CPL emission with a peak maximum at 643 nm. Moreover, the CPL bands depended on the aggregated state, which was identical to the emission c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…These facts, together with the short decay times associated with the luminescent bands (Table 1), made us confident in assigning them to 1 IL fluorescence transitions. It was observed that compound 3, containing the bulkier phosphine, displayed the common shape of TADBC monomer emission of 1, while 4 displayed a different peak-to-shoulder intensity proportion, which might have been an indication of the presence of aggregates [21,22]. Fluorescence decay times were measured for all the compounds using time-correlated single-photon counting (TC-SPC) ( Table 1).…”
Section: Compoundmentioning
confidence: 99%
“…These facts, together with the short decay times associated with the luminescent bands (Table 1), made us confident in assigning them to 1 IL fluorescence transitions. It was observed that compound 3, containing the bulkier phosphine, displayed the common shape of TADBC monomer emission of 1, while 4 displayed a different peak-to-shoulder intensity proportion, which might have been an indication of the presence of aggregates [21,22]. Fluorescence decay times were measured for all the compounds using time-correlated single-photon counting (TC-SPC) ( Table 1).…”
Section: Compoundmentioning
confidence: 99%
“…Circularly polarized luminescence (CPL) shows great potential as a probe to help understand excited-state chirality and for use in a range of practical photonic applications, including asymmetric synthesis, , optical storage devices, biological probes , and 3D displays . A variety of CPL materials have been reported, including small organic molecules, π-conjugated polymers, , chiral lanthanide complexes, aggregation-induced-emission gens and perovskite nanocrystals . To date, the main strategies used to produce CPL involve chiral blending, , supramolecular assemblies , and chiral liquid crystal encapsulation. , However, these strategies result in a limited dissymmetry factor ( g lum ) and unpredictable chirality .…”
Section: Introductionmentioning
confidence: 99%
“…This contrasting difference is most likely to arise from the extremely short fluorescence lifetime of perylene . Thus, one might imagine that the excited perylene is too short‐lived to encounter with another, mostly that of the ground state . Therefore, only a faint CPL was claimed to be observed from perylene‐based excimers to date .…”
Section: Figurementioning
confidence: 99%